2017
DOI: 10.1177/1525740117741170
|View full text |Cite
|
Sign up to set email alerts
|

Reading the Mind or Only the Story? Sharing Fiction to Develop ToM With Deaf Children

Abstract: In literature which discusses the Theory of Mind (ToM) of deaf children, the lens is usually focused on the child. Here, the lens is directed toward the practitioners and the potential they have to support the development of ToM. In considering a practice-focused approach, we report on the strategies used by five educators of five deaf children (aged between 4 and 8 years old) while using fiction books to explore the topic of thoughts and feelings. Observation of the book-sharing activities highlighted opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…For example, Wellman and Peterson (2013 ) showed that training based on thought bubbles improved ToM abilities in DoH children. Other studies found that ToM can be scaffolded with explicit instruction ( Stanzione & Schick, 2014 ), writing ( Chilton et al., 2019a , 2019b ) or through using fiction books to explore the topics of thoughts and feelings ( Chilton & Beazley, 2018 ). However, this issue was not tested directly in our study as we did not control for the quantity and quality of caregiver talk directed at children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wellman and Peterson (2013 ) showed that training based on thought bubbles improved ToM abilities in DoH children. Other studies found that ToM can be scaffolded with explicit instruction ( Stanzione & Schick, 2014 ), writing ( Chilton et al., 2019a , 2019b ) or through using fiction books to explore the topics of thoughts and feelings ( Chilton & Beazley, 2018 ). However, this issue was not tested directly in our study as we did not control for the quantity and quality of caregiver talk directed at children.…”
Section: Discussionmentioning
confidence: 99%
“…After the training, children scored higher on false belief scales than did the control groups without training. It was also demonstrated that ToM can be scaffolded with explicit instructions [49] or through using fiction books in order to engage the child in exploring the topic of thoughts and feelings [84]. Additionally, interactions between deaf parents and deaf children could serve as a model for interactions in the population of DoH children.…”
Section: Interventions To Promote Tom In Deaf Childrenmentioning
confidence: 99%